The fifth assassin - Meltzer, Brad (Grand Central Publishing, 2013)
Archivist Beecher White discovers a connection that may link the individuals responsible for the only four successful assassinations of American Presidents after discovering a modern-day killer who is recreating the assassins' crimes.